2015
DOI: 10.1155/2015/812934
|View full text |Cite
|
Sign up to set email alerts
|

Alloimmunization in Patients with Sickle Cell Disease in French Guiana

Abstract: This study in French Guiana assessed the frequency of alloimmunization to red cell antigens in sickle cell disease patients over 1995–2011 and identified the most common antibodies. A retrospective analysis of the transfusion history and medical records of 302 patients showed that 29/178 transfused patients had developed alloantibodies (16%). The most frequent alloantibodies were anti-LE1, anti-MNS1, anti-LE2, and anti-FY1 and were developed after transfusion of standard red cell units. The frequency of the cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
2
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 16 publications
2
9
2
1
Order By: Relevance
“…Anti‐M was the most frequent antibody, with a prevalence of 5·1%, whereas the prevalence of anti‐Le a and anti‐Le b antibodies was 2·3% and 1·7% respectively. This finding agrees with the results of a recent study in French Guiana, which reported anti‐M, anti‐Le a and anti‐Le b antibodies to be the most frequent, with a prevalence of 3·4%, 5·6% and 2·8%, respectively, among 178 SCD patients transfused mostly with blood from French European donors (Elenga & Niel, ). These antibodies are usually irregular natural immunoglobulin M (IgM), but DTT was not used and the so‐called pre‐warm technique is not implemented in France.…”
Section: Discussionsupporting
confidence: 92%
“…Anti‐M was the most frequent antibody, with a prevalence of 5·1%, whereas the prevalence of anti‐Le a and anti‐Le b antibodies was 2·3% and 1·7% respectively. This finding agrees with the results of a recent study in French Guiana, which reported anti‐M, anti‐Le a and anti‐Le b antibodies to be the most frequent, with a prevalence of 3·4%, 5·6% and 2·8%, respectively, among 178 SCD patients transfused mostly with blood from French European donors (Elenga & Niel, ). These antibodies are usually irregular natural immunoglobulin M (IgM), but DTT was not used and the so‐called pre‐warm technique is not implemented in France.…”
Section: Discussionsupporting
confidence: 92%
“…Twenty case reports and series that included 36 patients reported an improvement in hemoglobin values after treatment with IVIg, high-dose steroids, eculizumab, and/or rituximab. 59,61,[65][66][67][68][69][70][71][72][73][74][75][76][77][78][79] Regarding mortality, 1 retrospective study compared 53 patients who received supportive care only with 46 patients who received an immunosuppressive regimen and found 3 deaths in each group. 80 Another retrospective study examined 23 DHTR episodes, with 4 episodes managed by supportive care alone, 5 with immunosuppression with or without additional red cell transfusion, and 14 with red cell transfusion alone.…”
Section: Recommendationmentioning
confidence: 99%
“…The authors explained that since blood cannot be collected locally, use of blood mostly from French Caucasian blood donors is causing alloimmunization in the Guianese population due to ethnic/geneticdifferences 13 . Natukunda et al 6 reported that the rate of RBC alloimmunization in Ugandan SCD patients was 6.1%.…”
Section: Discussionmentioning
confidence: 99%
“…Many factors should be considered to minimize alloimmunization prevalence in this group of patients who need more frequent transfusions. The main factors which increase alloimmunization risk include increased patient age 3,11 , female gender 2,14 , history of pregnancy 2,6 , not applying leukoreduction 15 , use of long term stored blood products 14,15 , the number of transfused RBC units 2,14 , transfusion for acute vasoocclusive indications and elevated inflammatory status of the patients 2 , ethnic/genetic differences 3,6,13 .…”
Section: Discussionmentioning
confidence: 99%